Magnetic properties and magnetic anisotropy of two-dimensional organometallic framework. (March 2019) - Li, Xu; Long, Xia; Liu, Tian; Zhu, Guojun; Cao, Juexian
Abstract: By means of first-principles calculations together with torque method, we investigated the magnetic moment and magnetocrystalline anisotropy energy (MAE) for monolayers of organometallic framework TM3 C12 S12 with transition metal element TM (nd m with n = 3–5 and m = 4–8). According to square planar ligand field with weak interaction, the magnetic moment follows -|m-5|+3 for 3d transition metals. Interestingly, we find that Re3 C12 S12 has huge MAE about 13.54 meV with an easy axis perpendicular to TM3 C12 S12 plane. Moreover, our calculations pointed out that the MAE of Re3 C12 S12 can further enhance to 20.97 meV with tensile strain 5%. Our results provide a reliable guideline to manipulate the MAE of the magnetic materials in magnetic storage devices. Highlights: A novel ordering structure 2D material TM3 C12 S12 with an outstanding MAE. The magnetic moment can be explained by the ligand field theory. Re3 C12 S12 has huge MAE about 13.54 meV. The MAE of Re3 C12 S12 can further enhance to 20.97 meV with tensile strain 5%.